Underwear: fashion in detail - Lynn, Eleri.; Davis, Richard; Davis, Leonie. (V&A, 2010)
Chronicles the history of women's and men's underwear from the sixteenth century to the present, with color photographs, sketches, and historical notes for each garment.
Eleri Lynn ; photographs by Richard Davis ; drawings by Leonie Davis.
Keywords: Underwear; History